NEONATAL BILATERAL HYPHEMA: A RARE PRESENTATION AND CLINICAL IMPLICATIONS: NEONATAL BILATERAL HYPHEMA - Vasović, Dolika D.; Pantelić, Jelica; Rašić, Dejan M. (Srpski medicinski časopis Lekarske komore, 2025)
Introduction: Neonatal hyphema, defined as intraocular bleeding into the anterior chamber, is a rare condition that requires immediate ophthalmologic evaluation. Unlike traumatic hyphema commonly seen in older children and adults, neonatal hyphema is typically associated with non-traumatic etiologies such as birth-related mechanical stress, hematologic disorders, congenital infections, or vascular anomalies. Bilateral involvement is particularly uncommon and necessitates a comprehensive systemic and ophthalmologic workup to rule out serious underlying pathology.Case report: A female neonate was delivered at term via spontaneous vaginal delivery with normal Apgar scores and without perinatal complications. Shortly after birth, blood was observed in the anterior chambers of both eyes, more prominently in the right eye. Ophthalmologic examination confirmed bilateral hyphema with preserved corneal clarity. Systemic evaluation including complete blood count, coagulation studies, and TORCH serology ruled out coagulopathies and congenital infections. The patient was treated conservatively with topical atropine and corticosteroids. During hospitalization, the hyphema gradually resolved without evidence of elevated intraocular pressure or synechiae formation. The newborn was discharged with scheduled ophthalmologic follow-up to monitor for potential late complications.Conclusion: This case underscores the importance of early recognition and multidisciplinary management of neonatal hyphema, particularly when both eyes are affected. Although birth trauma remains a common cause, thorough diagnostic evaluation is essential to exclude hematologic and infectious etiologies. Given the rarity of bilateral neonatal hyphema, additional case reports and studies are needed to enhance understanding of its etiology, optimal management, and long-term outcomes.
Keywords: neonatal hyphema; intraocular hemorrhage; birth trauma; congenital infections; neonatal hematologic disorders